The Experience of the Creation of Educational IT Space of the Region - Valentyna Khivrych (International Journal of Research in E-Learning, 2015)
The article deals with the modern approaches to the use of information and communication technologies in the educational process, extracurricular activities and management at the regional level in order to enhance the creative potential of students, teachers and administrators. The article has described the conceptual bases of creating an information-educational environment of the region as a platform for information and achievement exchange between educators and the administration of the region. It specifies the technology of implementing the content and technology component of the information-educational environment of the region and its main functional components. We suggest the implementation model of the effective management of educational institutions in the form of a unified system for collecting, processing and storing valid statistical and operational information on the activities of pre-school, comprehensive educational institutions and territorial units of education management (in districts and cities). The article has described the integrated tools and technologies that are designed to ensure the educational needs of both students and teachers. We also suggest the model of a single control center for the information-educational environment of the region that organizes support for its exploitation and development.